The Effect Of Monthly Budget Use And Saving Habits On Generation Z's Personal Fund Management - Kasmanto Miharja; Ade Sri Mulyani (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to analyze the influence of monthly budgeting and saving habits on personal financial management in Generation Z. Personal financial management is an important aspect for Generation Z because this age group is faced with various consumer needs and the development of digital technology that influences financial spending patterns. The use of a monthly budget is understood as an individual's ability to plan and manage income and expenses in a structured manner, while saving habits are defined as the behavior of setting aside a portion of income regularly for future needs. This study uses a quantitative method with data collection techniques through distributing questionnaires to Generation Z respondents from various educational and occupational backgrounds. The data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results show that the use of a monthly budget and saving habits have a positive and significant effect on personal financial management of Generation Z. Thus, the better the ability to prepare a monthly budget and the more consistent the saving habits, the better the personal financial management carried out by Generation Z